Person-centered diagnosis and treatment in mental health : a model for empowering clients - Ladd, Peter D. (Jessica Kingsley Publishers, 2012)
Clients with mental health conditions are often diagnosed and treated using a strictly medical model of diagnosis, with little input from the client themselves. This reference manual takes a person-centered, holistic approach to diagnosis and treatment, seeing the client as the unrecognized expert on their condition and encouraging their collaboration. This qualitative approach aims to find meaning in the experiences of the client, exploring the reasons behind their feelings and behaviour and taking the whole person into account. Designed to complement DSM assessments, the manual covers severa.